Elfn1-Induced Constitutive Activation of mGluR7 Determines Frequency-Dependent Recruitment of Somatostatin Interneurons - Stachniak, Tevye Jason (J Neurosci, 2019)
Excitatory synapses onto somatostatin (SOM) interneurons show robust short-term facilitation. This hallmark feature of SOM interneurons arises from a low initial release probability that regulates the recruitment of interneurons in response to trains of action potentials. Previous work has shown that Elfn1 (extracellular leucine rich repeat and fibronectin Type III domain containing 1) is necessary to generate facilitating synapses onto SOM neurons by recruitment of two separate presynaptic components: mGluR7 (metabotropic glutamate receptor 7) and GluK2-KARs (kainate receptors containing glutamate receptor, ionotropic, kainate 2). Here, we identify how a transsynaptic interaction between Elfn1 and mGluR7 constitutively reduces initial release probability onto mouse cortical SOM neurons. Elfn1 produces glutamate-independent activation of mGluR7 via presynaptic clustering, resulting in a divergence from the canonical “autoreceptor” role of Type III mGluRs, and substantially altering synaptic pharmacology. This structurally induced determination of initial release probability is present at both layer 2/3 and layer 5 synapses. In layer 2/3 SOM neurons, synaptic facilitation in response to spike trains is also dependent on presynaptic GluK2-KARs. In contrast, layer 5 SOM neurons do not exhibit presynaptic GluK2-KAR activity at baseline and show reduced facilitation. GluK2-KAR engagement at synapses onto layer 5 SOM neurons can be induced by calmodulin activation, suggesting that synaptic function can be dynamically regulated. Thus, synaptic facilitation onto SOM interneurons is mediated both by constitutive mGluR7 recruitment by Elfn1 and regulated GluK2-KAR recruitment, which determines the extent of interneuron recruitment in different cortical layers. SIGNIFICANCE STATEMENT This study identifies a novel mechanism for generating constitutive GPCR activity through a transsynaptic Elfn1/mGluR7 structural interaction. The resulting tonic suppression of synaptic release probability deviates from canonical autoreceptor function. Constitutive suppression delays the activation of somatostatin interneurons in circuits, necessitating high-frequency activity for somatostatin interneuron recruitment. Furthermore, variations in the synaptic proteome generate layer-specific differences in facilitation at pyr → SOM synapses. The presence of GluK2 kainate receptors in L2/3 enhances synaptic transmission during prolonged activity. Thus, layer-specific synaptic properties onto somatostatin interneurons are mediated by both constitutive mGluR7 recruitment and regulated GluK2 kainate receptor recruitment, revealing a mechanism that generates diversity in physiological responses of interneurons.